Microwave co-torrefaction of waste oil and biomass pellets for simultaneous recovery of waste and co-firing fuel. (December 2021) - Yek, Peter Nai Yuh; Chen, Xiangmeng; Peng, Wanxi; Liew, Rock Keey; Cheng, Chin Kui; Sonne, Christian; Sii, How Sing; Lam, Su Shiung
Abstract: The low bulk density and heating value of biomass pellets limit their application as a co-firing fuel and a partial substitute fuel for high-efficiency coal boilers. In this study, we develop an innovative microwave co-torrefaction (MCT) process by combining microwave heating and torrefaction to convert palm waste fruit bunch pellets and used cooking oil (UCO) into torrefied biomass pellets as an alternative fuel. Microwave heating requires a shorter torrefaction duration of only 6–8 min compared with a conventional furnace (20 min) to attain the desired high process temperatures ranging from 200 °C to 300 °C. Torrefied biomass pellets produced from MCT yield less volatile matter (33–49 wt%) and lower oxygen contents (23.1–40.1 wt%) compared with those produced from conventional torrefaction. By conventional torrefaction at 300 °C, the highest fuel ratio of torrefied biomass pellets obtained is 2.0. MCT yields the desired energy yield of 98.1% at 250 °C, the highest fuel ratio of 1.9, and a heating value of 26.4 MJ/kg at 300 °C. MCT exhibits a lower activation energy of 12.0 kJ/mol compared with that of conventional co-torrefaction (13.6 kJ/mol), indicating that MCT can be performed at a relatively low operating temperature and with low energy consumption. These results indicate the potential of microwave heating for performing the co-torrefaction of biomass pellets using UCO as an economical approach to produce desirable pellet fuel from waste and biomass materials. Graphical abstract: Image 1 Highlights: Microwave co-torrefaction produces high energy co-firing fuel (up to 26.4 MJ/kg). Microwave co-torrefaction resulted in a low activation energy (12 kJ/mol). Microwave heating allows rapid heating and short process time. Torrefied pellet shows the highest heating value (26.4 MJ/kg) at 300 °C. Microwave co-torrefaction is a promising approach to produce solid fuel.